Recovery of precious metals from spent Mo-Co-Ni/Al2O3 catalyst in organic acid medium: Process optimization and kinetic studies - Arslanoglu, Hasan; Yaras, Ali (Taylor & Francis Inc, 2019)
In present study, the leaching kinetics of the spent Mo-Co-Ni/Al2O3 catalyst was investigated in the presence of formic acid as an organic leaching agent. Firstly, the spent catalyst was roasted in different roasting temperature (200-700 degrees C) and time (15-240 min), the maximum metal extraction was achieved that at 500 degrees C with 90 min. Then, the leaching experiments were carried out to determine the influences of process parameters following; particle size, liquid/solid ratio, formic acid concentration, leaching temperature, leaching time and stirring speed. According to the experimental results, the highest dissolution rates of molybdenum (Mo, 75.82%), cobalt (Co, 96.81%), nickel (Ni, 93.44%) and aluminum (Al, 19.46%) were reached under optimum experimental conditions; particle size thorn75 degrees 30 mm; liquid/ solid ratio 10 ml/g; formic acid concentration 0.6M; leaching temperature 80 degrees C; leaching time 90 min and stirring speed 300 r/min. Moreover, the leaching kinetics clearly reveal that the leaching reaction is controlled by liquid film diffusion and that the activation energy values (Ea) of Co, Ni, Mo and Al were to be 24.49, 25.98, 32.36 and 33.47 kJ/mol, respectively. In conclusion, the leaching process can be conducted in the presence of formic acid for the various industrial wastes in similar structure and composition to Mo-Co-Ni/Al2O3 spent catalyst.
Keywords: spent catalyst; molybdenum; cobalt; nickel; leaching; kinetic